Comparative characteristics of the fauna of terrestrial vertebrates of the Zagatala Nature Reserve (Azerbaijan) and the Lishan Nature Reserve (the People's Republic of China) - Mahluga M. Yusifova; Narmina A. Sadigova; Gunel R. Sariyeva; Jing Weitao; Nigar A. Sultanova; Kamala G. Nuriyeva; Sona A. Osmanova; Saltanat A. Aghayeva (Acta Biologica Sibirica, 2024)
This study aims to compare terrestrial vertebrate mammals in two protected areas located in different countries, each characterized by unique natural-ecological conditions and disparate management methods. Research focuses on terrestrial vertebrates of the Lishan Nature Reserve in the People’s Republic of China (24,200 hectares) and the Zagatala Nature Reserve in the Republic of Azerbaijan (47,349 hectares). We examine various indicators, such as size, weight, age, habitat, altitude, climate, and eating habits, to understand the factors that contribute to the differences between the two reserves. Field research was conducted from July 6–10, 2022, in the Zagatala Reserve and from June 15–21, 2023, in the Lishan Reserve. A systematic literature review was performed on the scientific, theoretical, and methodological foundations of protected area research. Additionally, we analyzed the natural and ecological characteristics (relief, climate, hydrography, soil cover, and vegetation) of both reserves and explored the taxonomy and distribution of terrestrial vertebrate species. We specifically studied rare and endemic species that inhabit these reserves, culminating in a comparative analysis of the fauna of amphibians and mammals in both locations, focusing on their size, weight, age, habitat, altitude, climate, and dietary patterns.